2011
DOI: 10.3198/jpr2010.04.0194crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘L 01–299’ Sugarcane

Abstract: ‘L 01–299’ (Reg. No. CV‐141, PI 659071) sugarcane (a complex hybrid of Saccharum officinarum L., S. barberi Jeswiet, S. spontaneum L., and S. sinense Roxb. amend. Jeswiet) was released on 28 Aug. 2009 by the Louisiana State University Agricultural Center in cooperation with the USDA‐ARS and the American Sugarcane League, Inc. L 01–299 was released because of its high sugar and cane yields, erectness, and excellent ratooning ability. The cross for L 01–299 (XL96–402) was made on 22 Oct. 1996. Early‐stage clonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…Thus, we have 3 yr of plant‐cane data, 2 yr of first‐ratoon data, and 1 yr of second‐ratoon data for L 03‐371. In the plant‐cane crop, the new cultivar, L 03‐371, had a significantly higher sugar yield than the commercial cultivars LCP 85‐384, Ho 95‐988 (Tew et al, 2005a), HoCP 96‐540, L 97‐128 (Gravois et al, 2008), and L 01‐299 (Gravois et al, 2011); its sugar yield was similar to that of the other cultivars. In the first‐ratoon crop, the sugar yield of L 03‐371 was significantly less than that of L 01‐299 and significantly greater than the sugar yields of LCP 85‐384, Ho 95‐988, and L 97‐128.…”
Section: Characteristicsmentioning
confidence: 85%
“…Thus, we have 3 yr of plant‐cane data, 2 yr of first‐ratoon data, and 1 yr of second‐ratoon data for L 03‐371. In the plant‐cane crop, the new cultivar, L 03‐371, had a significantly higher sugar yield than the commercial cultivars LCP 85‐384, Ho 95‐988 (Tew et al, 2005a), HoCP 96‐540, L 97‐128 (Gravois et al, 2008), and L 01‐299 (Gravois et al, 2011); its sugar yield was similar to that of the other cultivars. In the first‐ratoon crop, the sugar yield of L 03‐371 was significantly less than that of L 01‐299 and significantly greater than the sugar yields of LCP 85‐384, Ho 95‐988, and L 97‐128.…”
Section: Characteristicsmentioning
confidence: 85%
“…Greater sucrose yield was attributed to 28-37% more cane yield than HoCP 96-540 and HoCP 04-838, and was likely due to more millable stalks in the first and second-ratoon crop (Table 2). Gravois et al (2011) reported L 01-299 stalk population increased 18% from plant cane to first ratoon, 6% from first to second ratoon, and 1% from second to third ratoon when averaged across ten locations; however, the HoCP 96-540 stalk population decreased 1 and 25% from plant cane to first ratoon and from second to third ratoon, respectively.…”
Section: Field Studymentioning
confidence: 87%
“…The experimental design was a split-plot factorial arrangement of ripener treatments and cultivars with four replications. Whole-plots were ripener treatment with three levels and subplots were nine sugarcane cultivars HoCP 96–540 [9], L 99–226 [10], HoCP 00–950 [11], L 01–283 [12], L 01–299 [13], HoCP 04–838 [14], Ho 07–613, Ho 09–804 [15], and HoCP 09–840 that were randomly allocated to subplots within each whole plot. Glyphosate (Roundup WeatherMax, Monsanto, St. Louis, MO) and trinexapac-ethyl (Moddus, Syngenta Crop Protection, Greensboro, NC) were applied at a rate of 210 g ae ha -1 and 200 g ai ha -1 , respectively.…”
Section: Methodsmentioning
confidence: 99%